Insights on DRGs, guideline compliance and economic sustainability. The case of mastectomy with immediate breast reconstruction - Specchia, M. L.; Di Pilla, G.; Limongelli, P.; Salgarello, M.; Masetti, R.; Bellantone, R. D. A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Immediate breast reconstruction is recommended for eligible patients undergoing mastectomy, raising the issue of economic sustainability of both mastectomy and breast reconstruction performed within the same hospitalization, as opposed to two surgical procedures in two different hospitalizations. Study design. A retrospective analysis was conducted to compare economic sustainability of mastectomies with or without immediate breast reconstruction. Methods. Economic data on hospitalizations for mastectomy in a Teaching Hospital between 1 January 2019 and 31 March 2021 were analyzed to assess their sustainability. Results. 338 admissions were selected (63.9% with immediate breast reconstruction (CI 99%: 57.2% to 70.6%). Compared to mastectomy alone, mastectomy with immediate breast reconstruction had higher cost of € 2,245 (p < 0.001), with operating rooms and devices as main cost drivers. Current reimbursements rates (which are the same for mastectomy alone and for mastectomy with immediate breast reconstruction) led to an average loss of € 1,719 for each mastectomy with immediate breast reconstruction. Conclusion. Current DRGs reimbursement rates for hospital admissions for breast cancer surgery do not guarantee immediate breast reconstruction’s economic sustainability. DRGs system should be revised, or other solutions as bundled payment should be implemented in the light of the costs of innovation in healthcare, considering mastectomy and breast reconstruction steps in a path of linked actions aimed at improving patients’ health.